INNV-07. TTFIELDS TREATMENT OF GLIOSARCOMA AND RECURRENT ANAPLASTIC OLIGODENDROGLIOMA. (12th November 2021) - Blondin, Nicholas; Fulbright, Robert; Huttner, Anita; Moliterno-Gunel, Jennifer
Abstract: INTRODUCTION: The Optune device delivers tumor treating fields (TTFields) and is considered as a standard of care for newly diagnosed and recurrent glioblastoma patients. The efficacy of Optune in other glioma subtypes, such as gliosarcoma and anaplastic oligodendroglioma, is still unclear. In this small case series, we present the clinical, pathologic and radiographic findings of two patients who utilized Optune and had improved outcomes compared to historical controls. CASE 1: A 49 year old woman underwent resection of a right temporal lobe gliosarcoma in November 2017. She received conventional radiation therapy with concurrent temozolomide, which was complicated by significant thrombocytopenia and leukopenia. She initiated Optune as monotherapy six weeks after completing radiation, and used the device for 24 months. She still has not had a recurrence, now 3.5 years since her initial diagnosis. CASE 2: A 46 year old woman underwent resection of a right frontal lobe oligodendroglioma, WHO Grade 2, in September 2011. She received one cycle of temozolomide in April 2014, complicated by thrombocytopenia, and no further chemotherapy was administered. In November 2017, she underwent resection of a new focus of enhancement at the margin of the resection cavity, which was confirmed to have transformed to WHO Grade 3. In August 2019, a radiographic progression of an enhancing nodule was observed. She initiated Optune as monotherapy in September 2019, and since that time, has had stable disease for 18 months. Optune treatment is still ongoing. CONCLUSIONS: In a case of newly diagnosed gliosarcoma, Optune monotherapy has contributed to progression-free and overall survival of 3.5 years to date. In a case of recurrent anaplastic oligodendroglioma, Optune monotherapy has achieved stable disease for at least 18 months. These cases demonstrate that Optune can be safely utilized in these glioma subtypes and contributed to improved survival outcomes in these two patients.